Precision control of flow rate in microfluidic channels using photoresponsive soft polymer actuators. Issue 11 (22nd May 2017) - Delaney, Colm; McCluskey, Peter; Coleman, Simon; Whyte, Jeffrey; Kent, Nigel; Diamond, Dermot
Abstract : Precision control of flow using photoresponsive hydrogels within fluidic channels was demonstrated by applying a PID algorithm. Abstract : A novel approach that allows control of flow in microfluidic channels with unsurpassed performance using light is described. Valve structures have been created using photoresponsive hydrogels based on spiropyran-functionalised pNIPAAm hydrogels photopolymerised around pillar structures within the channels. Valve actuation is controlled from outside the fluidic system using externally located LEDs. Highly precise and accurate flow rates can be selected by passing real-time flow rate measurements into a PID algorithm. The optimised algorithm also minimises overshoot of the selected flow rate, eliminates flow rate drift, and improves the system response time. In addition to the dramatic improvements in flow rate control, the set up enables the polymer actuation behaviour to be rapidly characterised. The power supply to the LED also provides a useful system diagnostic for monitoring the performance of the valve over time. For example, degradation in the valve actuation due to photodegradation will manifest as an increasing power requirement over time, enabling predictive failure thresholds to be established for particular actuator designs and polymer compositions.